Ambient seismic noise imaging of the lowermost mantle beneath the North Atlantic Ocean. Issue 2 (1st May 2020) - Retailleau, Lise; Boué, Pierre; Li, Lei; Campillo, Michel
SUMMARY: Body waves can be extracted from correlation functions computed from seismic records even at teleseismic distances. Here we use P and PcP waves from the secondary microseism frequency band that are propagating between Europe and the Eastern United States to image the core–mantle boundary (CMB) and D " structure beneath the North Atlantic. This study presents the first 3-D image of the lower mantle obtained from ocean-generated microseism data. Robustness of our results is evaluated by comparing images produced by propagation in both directions. Our observations reveal complex patterns of lateral and vertical variations of P -wave reflectivity with a particularly strong anomaly extending upward in the lower mantle up to 2600 km deep. We compare these results with synthetic data and associate this anomaly to a Vp velocity increase above the CMB. Our image aims at promoting the study of the lower mantle with microseism noise excitations.